Al–Mn–Fe intermetallic formation in AZ91 magnesium alloys: Effects of impurity iron. (March 2022) - Peng, L.; Zeng, G.; Xian, J.; Gourlay, C.M.
Abstract: The influence of iron on the formation of Al–Mn–Fe intermetallic compounds (IMCs) has been investigated in the solidification of Mg–9Al-0.7Zn-0.2Mn (wt.%, AZ91) with iron contents ranging from ∼0.001 to > 0.01 wt.% Fe. Four Al–Mn–Fe IMCs formed depending on the Fe-content and location in the crucible: B2–Al(Fe, Mn), Al8 Mn5, Al11 Mn4 and, at the bottom of crucibles, Al5 Fe2 . The four IMCs nucleated and grew on one another, producing multiphase particles. These usually contained numerous orientations that were all interrelated through simple orientation relationships that are discussed in terms of the similarities between the IMC crystal structures. The iron content affected the IMC phase fractions and the multiphase particle morphology. At low iron content, the Fe-rich B2 phase was encapsulated by a low-Fe Al8 Mn5 shell. With increasing iron content, the Fe-rich phases (B2 and Al5 Fe2 ) gradually became in direct contact with the α-Mg. The threshold Fe:Mn content for adequate corrosion performance is found to correlate approximately to where B2–Al(Fe, Mn) first becomes exposed to the α-Mg matrix. Highlights: Al–Mn–Fe IMCs nucleate on each other with interrelated orientation relationships. Al8 Mn5 and Al11 Mn4 grow to fully or partially cover the Fe-rich B2–Al(Fe, Mn) core. B2–Al(Fe, Mn) become in direct contact with α-Mg as Fe content increases. Threshold Fe:Mn for corrosion correlates to B2–Al(Fe, Mn) becoming exposed to α-Mg.